The Influence Of Compensation And Organizational Culture On Workforce Agility Mediated By Employee Engagement - Fitriana, Fitriana; Nurhayati, Mafizatun; Rahayu, Heffi Christya (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – This paper examines the influence of compensation and organizational culture on workforce agility, mediated by employee engagement, at Raja Ali Haji Maritime University (UMRAH). Methodology/approach – Data were collected via a survey focusing on the influence of compensation and organizational culture on workforce agility. The population consisted of 227 education personnel at UMRAH. The sample comprised 103 ASN education personnel from UMRAH.Findings – The study found that organizational culture is a key factor directly and significantly affecting workforce agility. This highlights the importance of fostering a strong organizational culture (BerAKHLAK) to enhance workforce agility at UMRAH, enabling the university to adapt to change. Novelty/value – To navigate the challenges of the VUCA world (volatility, uncertainty, complexity, and ambiguity), UMRAH needs to improve workforce agility to achieve its vision and mission. Contrary to expectations, compensation did not have a significant effect on workforce agility. Instead, organizational culture, an area that has not been a primary focus at UMRAH, proved to be a more influential factor in enhancing workforce agility.